Coats’ disease and retrobulbar haemodynamics - Zhao, Qi; Jonas, Jost B. (Acta ophthalmologica, 2016)
Purpose To study the retrobulbar haemodynamics in patients with Coats’ disease. Methods The clinical study included 43 patients with Coats’ disease. Using colour Doppler imaging, we measured the blood flow velocity in the ophthalmic artery (OA), central retinal artery (CRA) and posterior ciliary arteries (PCA), and recorded the peak systolic velocity (PSV), end diastolic velocity (EDV), time averaged maximum velocity (TAMX), pulsatility index (PI) and resistance indexes (RI). The unaffected contralateral eyes served as control group. The disease was graded into four stages. Results Compared to the contralateral eyes, the Coats’ disease affected eyes showed for the CRA a significant decrease in PSV (7.08 ± 1.38 cm/s versus 8.64 ± 1.45 cm/s; p < 0.001), EDV (2.03 ± 0.41 cm/s versus 2.52 ± 0.62 cm/s; p < 0.001) and TAMX (3.67 ± 0.96 cm/s versus 4.40 ± 1.22 cm/s; p = 0.003) and for the PCA a significant decrease in PSV (9.15 ± 1.87 cm/s versus 10.14 ± 1.61 cm/s; p = 0.01). Subgroup analysis revealed that the decrease in haemodynamic parameters existed mainly in patients with stage 3A2 and stage 3B of Coats' disease. Conclusions As measured by colour Doppler imaging, the retrobulbar blood vessels showed decreased haemodynamic parameters in patients with Coats’ disease on the affected side as compared to the contralateral unaffected side, in particular in advanced stages of the disease. Future studies may address the causes and effects of these haemodynamic changes.